A reversible and efficient probe for dual mode recognition of Al3+ and Cu2+ with logic gate behaviour: Crystal structure, theoretical and in-vivo bio-imaging investigations - Yadav P.; Kumar R.; Srikrishna S.; Kumar Pandey A.; Choudhury L.H.; Upadhyay C.; Singh V.P. (My University, 2025)
This work presents the synthesis, characterization, crystal structure and spectroscopic investigations of isophthalohydrazide based probe. Among various tested metal ions, the probe selectively detects Al3+ and Cu2+ in aqueous ethanol via fluorometric and colorimetric methods, respectively. It displays a fluorescence “turn-on” response with Al3+ and visual colour change from colourless to yellow with Cu2+. Sensing mechanism is explored with UV–Vis, fluorescence spectroscopy and 1H NMR titration, and confirmed with computational results. Suppression of C[dbnd]N isomerization and photo-induced electron transfer (PET) along with chelation enhanced fluorescence emission (CHEF) result in “turn-on” fluorescence with Al3+ while ligand to metal charge transfer (LMCT) accounts for visual colour change with Cu2+. Job's plot and HRMS confirm 1:2 (L:M) stoichiometry. The probe also exhibits efficient reversibility and reproducibility with EDTA which are successfully mimicked with combinatorial logic gate and truth table. Additionally, solid state applications and bio-imaging investigation on gut tissue of Drosophila 3rd instar larvae are performed. © 2021 Elsevier B.V.